The Jury is still out: A Comparison of AGG, Fujaba, and PROGRES - Fuß, Christian; Mosler, Christof; Ranger, Ulrike; Schultchen, Erhard (Electronic Communications of the EASST, 2007)
Graph transformation languages offer a declarative and visual programming method for software systems with complex data structures. Some of these languages have reached a level of maturity that allows not only conceptual but also practical use. This paper compares the three widespread graph transformation languages AGG, Fujaba, and PROGRES, considering their latest developments. The comparison is three-fold and regards conceptual aspects, language properties, and infrastructure features. Because of the different relevance of these aspects, we do not determine a clear winner but leave it to the reader.